Hospitals Strengthened Relationships with Close Partners After Joining Accountable Care Organizations - Everson, Jordan (Med Care Res Rev, 2018)
The strategies that hospitals participating in Medicare Accountable Care Organizations use to achieve quality and cost containment goals are poorly understood. One possibility is that participating hospitals could try to influence where their patients receive care. To test this hypothesis, we examined whether a hospital’s participation in a Medicare ACO was associated with changes in its patterns of patient sharing with other hospitals. Between 2010 and 2014, patient sharing across hospitals increased 23.3%. After controlling for hospital and regional factors, patient sharing increased 4.4% more at ACO hospitals than non-ACO hospitals (P=0.001 for difference). This increase occurred disproportionately among hospitals with which ACO hospitals already shared a high proportion of their patients prior to participation, and among hospitals in ACOs characterized as physician-hospital collaborations. The increased sharing of patients among closely affiliated hospitals may serve to achieve ACO quality and cost containment goals through increased inter-organizational coordination.